Tip enhanced Raman spectroscopy imaging of opaque samples in organic liquid. Issue 23 (26th May 2016) - Touzalin, T.; Dauphin, A. L.; Joiret, S.; Lucas, I. T.; Maisonhaute, E.
Abstract : We demonstrate the feasibility of Tip Enhanced Raman Spectroscopy in liquid for an upright illumination/collection configuration. Abstract : Implementation of Tip Enhanced Raman Spectroscopy in liquid is still a challenge. We demonstrate herein its feasibility in an upright illumination/collection configuration. Through a thin layer of organic solvent covering the sample, laser focussing on the tip is possible, enabling TERS imaging in liquid.